2008
DOI: 10.1007/s12144-008-9033-y
|View full text |Cite
|
Sign up to set email alerts
|

The Relations of Cognitive Triad, Dysfunctional Attitudes, Automatic Thoughts, and Irrational Beliefs with Test Anxiety

Abstract: Previous research has highlighted the important role of cognition in anxiety, including test anxiety. The present study explores the role of cognitive distortions and irrationality in test anxiety by studying the relationships among cognitive triad (core beliefs), dysfunctional attitudes (intermediate beliefs), negative automatic thoughts, irrational beliefs, debilitating test anxiety, and facilitating test anxiety in 138 undergraduates. Multiple regression analyses showed that only the cognitive triad as a wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 48 publications
5
27
0
16
Order By: Relevance
“…Negative thinking has been found to play a pivotal role in psychopathological states such as depression [3,11,[13][14][15][16][17][18] and anxiety [3,7,[17][18][19][20][21]. Indeed, studies have found a connection between the presence of negative thoughts and anxiety in clinically anxious adults [22] and children [23].…”
Section: Introductionmentioning
confidence: 99%
“…Negative thinking has been found to play a pivotal role in psychopathological states such as depression [3,11,[13][14][15][16][17][18] and anxiety [3,7,[17][18][19][20][21]. Indeed, studies have found a connection between the presence of negative thoughts and anxiety in clinically anxious adults [22] and children [23].…”
Section: Introductionmentioning
confidence: 99%
“…In such situations, parents do a lot to assist their children but they do not achieve as much as they wish, thus they perceive themselves as unable mothers or fathers and they feel hopelessness about the future. Spending long time periods for treatment, providing required care for the child in the house, confronting school and behavioral problems of the disable child, all lead to parents' hopelessness and anxiety (18,19). They are not able to participate in social activities due to the negative feedback they receive from others about their child.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of the mentioned inventory obtained for the whole scale was 0.95, for subscales of attitude towards oneself was 0.91, the world 0.81, and the future 0.93 by applying Cronbach's alpha. The simultaneous validity of the cognitive triad inventory was 0.77, through significant correlation with Beck's depression inventory (18). The mentioned inventory showed good validity and reliability in Iran and its Cronbach's alpha was 0.85 for the whole inventory, and 0.80, 0.73 and 0.81 for subscales of the attitude toward oneself, the world and the future, respectively (19).…”
Section: Cognitive Triad Inventorymentioning
confidence: 99%
“…Ona pozitivno korelira sa prokrastinacijom (Cassady & Johnson, 2002;Rosário et al, 2008), negativnim afektom (Bradley et al, 2010) i generalnim distresom (Matthews, Hillyard, & Campbell, 1999). Ovoj grupi pridružuju se i simptomi depresivnosti, anksioznosti i stresa (Bieling, Israeli, & Antony, 2004), kao i upotreba iracionalnih uverenja (Wong, 2008). Uprkos problemima u određivanju uzročno-posledičnih veza ispitne anksioznosti i uspeha, navedeni rezultati ipak daju osnov za pretpostavku da je ispitna anksioznost važan remetilački faktor testovnog postignuća kod studenata.…”
unclassified
“…Uprkos problemima u određivanju uzročno-posledičnih veza ispitne anksioznosti i uspeha, navedeni rezultati ipak daju osnov za pretpostavku da je ispitna anksioznost važan remetilački faktor testovnog postignuća kod studenata. Sa druge strane, ispitna anksioznost negativno korelira sa grupom pozitivnih psiholoških fenomena, među kojima su upotreba racionalnih uverenja (Wong, 2008), pozitivni afekat (Nelson & Knight, 2010), zadovoljstvo životom (Rajabi, Abolghasemi, & Abbasi, 2012) i subjektivni osećaj vitalnosti (Ryan & Frederick, 1997), ukazujući na to da je odsustvo ove forme anksioznosti značajno povezano sa psihološkim blagostanjem individue.…”
unclassified